Li ION CONDUCTING POLYMER BASED ON POLYVINYLIDENE FLUORIDE AND Li TRIFLATE - Evi Yulianti; Sudaryanto Sudaryanto; Heri Jodi; Deswita Deswita; Mashadi Mashadi (Jurnal Sains Materi Indonesia, 2013)
Li ION CONDUCTING POLYMER BASED ON POLYVINYLIDENE FLUORIDE AND Li TRIFLATE. A Series of polymer electrolyte based on Polyvinylidene Fluoride (PVDF) for solid state rechargeable lithium battery has been prepared by solution casting technique. Lithium triflate salt was used as filler with various compositions. Bulk nature and surface morphology of the polymer electrolytes were studied by X-Ray Diffractometer (XRD) and Scanning Electron Microscope (SEM), respectively. The thermal properties of polymer and salt were confirmed by Differential Scanning Calorimeter (DSC). The electrical properties of electrolyte polymer membrane were studied by using impedance spectrometer. It was found that the highest ionic conductivity was obtained for PVDF + Li Triflate 10%(w/w) which is 4.5411 x 10-3 S/cm. It was also found that there was peak of each composition in the loss tangent suggests the presence of relaxing dipoles in the polymer electrolyte films. The peak shifts towards higher frequency side suggesting the speed up of the relaxation time.